AMELIORATIVE EFFECTS OF SACCHAROMYCES CEREVISIAE (H.) ON HEMATOLOGICAL- BIOCHEMICAL PARAMETERS IN BROILER CHICKENS FED DIETS CONTAMINATED-NATURAL AFLATOXIN: HEMATOBIOCHEMICAL RESPONSE TO YEAST ADDITION TO BROILER DIET AS ANTI-AFLATOXIN - Mostafa, Ammar; Tammouz, Munzer; Ameen, Questan (Food and Feed Research, 2025)
This study evaluated the effects of supplementing two levels of Saccharomyces cerevisiae (H.) yeast in broiler diets naturally contaminated with aflatoxins (32 ppb), produced by Aspergillus flavus L. on hematological and biochemical parameters. A total of 200 one-day-old Ross 308 chicks were randomly assigned to four groups, each with five replicates of 10 birds. The negative control group (T1) received an uncontaminated diet, whereas the positive control (T2) was fed an aflatoxin-contaminated diet without additives. Groups T3 and T4 received contaminated diets supplemented with S. cerevisiae at 0.1% and 0.2% levels, respectively. Feeding broilers, a naturally aflatoxin-contaminated diet (32 ppb) adversely affected hematological and biochemical parameters (p ≤ 0.01), indicating compromised health and physiological status. Dietary supplementation, particularly at the 0.2% level, significantly improved hematological and biochemical profiles compared with the positive control (p ≤ 0.01). Improvements were observed in red blood cell counts (26%, 17%), white blood cell counts (12%, 9%), hemoglobin concentrations (6%, 5%), total protein levels (33%, 13%), albumin (20%, 7%), and globulin (47%, 26%), along with reductions in heterophil-to-lymphocyte ratios (23%, 21%), glucose concentrations (4%, 3%), and total cholesterol (6%, 5%) on days 21 and 42, respectively. These results demonstrate that dietary supplementation with 0.2% S. cerevisiae effectively mitigates the adverse effects of natural aflatoxin contamination on hematological and biochemical parameters in broiler chickens.
Keywords: blood cell; natural aflatoxins; Ross 308 broiler; total cholesterol; yeast